Analogue experiments on releasing and restraining bends and their application to the study of the Barents Shear Margin - Gabrielsen, Roy Helge; Giannenas, Panagiotis Athanasios; Sokoutis, Dimitrios; Willingshofer, Ernst; Hassaan, Muhammad; Faleide, Jan Inge (Solid Earth, 2023)
International audience The Barents Shear Margin separates the Svalbard and Barents Sea from the North Atlantic. During the break-up of the North Atlantic the plate tectonic configuration was characterized by sequential dextral shear, extension, and eventually contraction and inversion. This generated a complex zone of deformation that contains several structural families of overlapping and reactivated structures. A series of crustal-scale analogue experiments, utilizing a scaled and stratified sand-silicon polymer sequence, was used in the study of the structural evolution of the shear margin. The most significant observations for interpreting the structural configuration of the Barents Shear Margin are the following. Prominent early-stage positive structural elements (e.g. folds, push-ups) interacted with younger (e.g. inversion) structures and contributed to a hybrid final structural pattern. Several structural features that were initiated during the early (dextral shear) stage became overprinted and obliterated in the subsequent stages. All master faults, pull-apart basins, and extensional shear duplexes initiated during the shear stage quickly became linked in the extension stage, generating a connected basin system along the entire shear margin at the stage of maximum extension. The fold pattern was generated during the terminal stage (contraction-inversion became dominant in the basin areas) and was characterized by fold axes striking parallel to the basin margins. These folds, however, strongly affected the shallow intra-basin layers. The experiments reproduced the geometry and positions of the major basins and relations between structural elements (fault-and-fold systems) as observed along and adjacent to the Barents Shear Margin. This supports the present structural model for the shear margin. © Copyright: